2017
DOI: 10.1007/s00253-016-8085-4
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of alkaline polygalacturonate lyase from Bacillus subtilis on the surface of bacterial polyhydroxyalkanoate nano-granules

Abstract: Alkaline polygalacturonate lyase (PGL), one of the pectinolytic enzymes, has been widely used for the bioscouring of cotton fibers, biodegumming, and biopulp production. In our study, PGL from Bacillus subtilis was successfully immobilized on the surface of polyhydroxyalkanoate (PHA) nanogranules by fusing PGL to the N-terminal of PHA synthase from Ralstonia eutropha via a designed linker. The PGL-decorated PHA beads could be simply achieved by recombinant fermentation and consequent centrifugation. The fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The results indicated that the target fused proteins were immobilized on the PHA granules, comprising approximately 5% of the total attached protein (Table 1). The ratio of fused protein was higher than 0.985% described previously [6].
Fig.
…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The results indicated that the target fused proteins were immobilized on the PHA granules, comprising approximately 5% of the total attached protein (Table 1). The ratio of fused protein was higher than 0.985% described previously [6].
Fig.
…”
Section: Resultsmentioning
confidence: 51%
“…These surface proteins have attracted much attention and inspired investigations to explore them as anchoring tags to attach proteins and peptides to the surface of BNPs. The engineered BNPs are exciting prospects for drug targeting [5], bio-catalysis [6], biochemical separation [7] and bioremediation [8]. Compared with existing chemical immobilization technologies [9, 10], surface engineering of BNPs is highly advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…The bioscouring assay exhibited that PEL3 can obviously improve the wettability and softness of fabrics, suggesting its potential application in textile industry (Wang et al, 2018). The first case for enzyme immobilization of pectate lyases (PGL) from B. subtilis was reported by Ran et al (2017), PGL was successfully immobilized on the surface of polyhydroxyalkanoate (PHA) nanogranules by fusing PGL to the N-terminal of PHA synthase from Ralstonia eutropha via a designed linker. The activity of PGL-PHA compared to the free PGL was decreased almost 15%, and immobilization process did not affect the optimal pH and temperature of the free Pels, which was also observed with PEL3/Cu 3 (PO 4 ) 2 hybrid nanoflowers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the encouraging proof-of-concept results adapting the PHA particle technology for development of immobilized enzymes for uses in the food industry (Moldes et al, 2004;Rasiah and Rehm, 2009;Ran et al, 2017Ran et al, , 2019, production of commodity chemicals (Jahns and Rehm, 2015;Yang et al, 2015;Seo et al, 2016), production of fine chemicals Chen S. Y. et al, 2014;Tan et al, 2019), and bioremediation (Robins et al, 2013;Hooks and Rehm, 2015;Li et al, 2019), it is anticipated that research prototypes will be developed into industrial products.…”
Section: Potential Industrial Applications Of the Pha Particle Technomentioning
confidence: 99%